Lipopolysaccharide (LPS) recognition in macrophages. Participation of LPS-binding protein and CD14 in LPS-induced adaptation in rabbit peritoneal exudate macrophages. - Mathison, J (1993)
Exposure of rabbit peritoneal exudate macrophages (PEM) or whole blood to picomolar concentrations of LPS induces adaptation or hyporesponsiveness to LPS. Because of the importance of plasma LPS-binding protein (LBP) and the macrophage cell membrane protein CD14 in recognition of LPS, we examined the effect of LBP on LPS-induced adaptation in PEM. PEM exposed to LPS in the presence of LBP for 8 h were markedly less responsive to subsequent stimulation by LPS than monocytes/macrophages (M phi) adapted in the absence of LBP. LPS-induced expression of TNF was sharply reduced in LBP-LPS-adapted PEM, but in contrast these cells remained fully responsive to Staphylococcus aureus peptidoglycan. We considered that specific hyporesponsiveness in LPS-adapted M phi or in blood monocytes could be due to decreased expression of CD14 or diminished binding of LBP-LPS complexes to CD14. However, flow cytometry analysis revealed only minimal reduction of CD14 expression or CD14-dependent binding of a fluorescent LPS derivative when normo- and hyporesponsive cells were compared. These results show that complexes of LPS and LBP are more effective than LPS alone in inducing adaptation to LPS, and LPS-induced hyporesponsiveness probably results from changes in cellular elements distinct from CD14 that are involved in either LPS recognition or LPS-specific signal transduction.